2021
DOI: 10.4018/jgim.20210701.oa10
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Artificial Intelligence on Branding

Abstract: Understanding the growth paths of artificial intelligence (AI) and its impact on branding is extremely pertinent of technology-driven marketing. This explorative research covers a complete bibliometric analysis of the impact of AI on branding. The sample for this research included all 117 articles from the period of 1982-2019 in the Scopus database. A bibliometric study was conducted using co-occurrence, citation analysis and co-citation analysis. The empirical analysis investigates the value propositions of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 135 publications
0
21
0
1
Order By: Relevance
“…Moreover, previous research has indicated that users' perceptions of quality are among the theoretical foundations of technology acceptance (Varsha et al, 2021), in this case, good quality services and AI. Future research initiatives could undertake a more comprehensive exploration of the interplay between 'customer' and 'data,'…”
Section: Future Research Agendamentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, previous research has indicated that users' perceptions of quality are among the theoretical foundations of technology acceptance (Varsha et al, 2021), in this case, good quality services and AI. Future research initiatives could undertake a more comprehensive exploration of the interplay between 'customer' and 'data,'…”
Section: Future Research Agendamentioning
confidence: 99%
“…Over the last few decades, the human race has faced a new revolution, the Fourth Industrial Revolution (Faruk et al, 2021). Technical innovations in various fields have attracted great interest from researchers, in fields such as marketing (Abhishek & Srivastava, 2021; Chintalapati & Pandey, 2021; Davenport et al, 2020; Jarek & Mazurek, 2019; Randhawa et al, 2016; Vlačić et al, 2021), business‐to‐business marketing models (Chen et al, 2016; Chen, Jiang, et al, 2022; Han et al, 2021; Jiang, 2021; Kim & Moon, 2021; Saura et al, 2021), branding (Cheng & Jiang, 2021; Varsha et al, 2021), product management (Duong et al, 2022; Haefner et al, 2021) and the employment of social media/influencers for promotional purposes (Abhishek & Srivastava, 2021; Dwivedi et al, 2021; Voorveld et al, 2018; Ye et al, 2021; Zahay, 2021). Artificial intelligence is a flourishing phenomenon that is attracting intense interest from the public, companies and researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of detecting and averting cyberattacks is growing as we move to a post-pandemic world that has normalized new organizational models, such as working from home. The complexity is exacerbated by the advent of technologies such as artificial intelligence (Akter et al ., 2021; Varsha et al ., 2021), the Internet of Things (Huang et al ., 2021; Peng et al ., 2021), blockchain ( Teoh, 2022) and other highly interoperable systems (Lee et al ., 2021; Xanthidis and Xanthidou, 2021). Not surprisingly, disruptions and shortages due to the COVID-19 pandemic that revealed weaknesses in inter-organizational systems forced increased focus on the resilience of supply chains, resulting in a plethora of research on the topic (Tukamuhabwa et al ., 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…UPS and FedEx developed blockchain pilot projects to enhance their logistics systems. Furthermore, AI and big data technologies can be leveraged to analyze on-chain data and provide near real-time analytics and recommendations to relevant stakeholders through customized dashboards (Rabah, 2018;Sultana et al, 2021;Varsha et al, 2021).…”
Section: The Iot and Blockchain Technologiesmentioning
confidence: 99%